Numerical study on the influence of artificial internal stress relief groove on fretting fatigue in a shrink-fitted assembly. (November 2020) - Erena, Diego; Vázquez, Jesús; Navarro, Carlos; Talemi, Reza
Abstract: Fretting fatigue failure occurs in shrink-fitted assemblies due to the combination of high stresses and relative displacements near the contact edge. Due to these high stresses, fatigue crack initiates followed by crack propagation until final rupture. Additive manufacturing (AM) is a game changing technology, which enables new component capabilities that cannot be manufactured with conventional techniques. This research work analyses numerically the influence of an artificial internal stress relief toroidal groove inside a shrink-fitted shaft, which could be manufactured using AM technology. Due to the toroidal void, the stress/strain fields are redistributed improving the fretting fatigue crack initiation and propagation lifetimes. To do so, 2D finite element models are created in Abaqus software with and without the internal groove. To estimate the fretting fatigue initiation and propagation lifetime and crack propagation direction, critical plane methods are used. In terms of the crack propagation, eXtended Finite Element Method (XFEM) is used to simulate mixed mode crack advancing in a single mesh structure. Finally, the obtained results with and without void were compared concluding with significant improvements in terms of total fatigue lifetime. Highlights: Shrink-fitted shaft fretting fatigue palliative. Evaluation and comparison of crack propagation direction methods. Analysis of crack propagation direction using XFEM. Voids could delay crack initiation and propagation stages.